Neural Responses of Acupuncture for Treating Functional Dyspepsia: An fMRI Study - Dong, Xiaohui; Yin, Tao; Yu, Siyi; He, Zhaoxuan; Chen, Yuan; Ma, Peihong; Qu, Yuzhu; Yin, Shuai; Liu, Xiaoyan; Zhang, Tingting; Huang, Liuyang; Lu, Jin; et al. (Frontiers in Neuroscience, 2022)
Different acupoints exhibiting similar therapeutic effects are a common phenomenon in acupuncture clinical practice. However, the mechanism underlying this phenomenon remains unclear. This study aimed to investigate the similarities and differences in cerebral activities elicited through stimulation of CV12 and ST36, the two most commonly used acupoints, in the treatment of gastrointestinal diseases, so as to partly explore the mechanism of the different acupoints with similar effects. Thirty-eight eligible functional dyspepsia (FD) patients were randomly assigned into either group A (CV12 group) or group B (ST36 group). Each patient received five acupuncture treatments per week for 4 weeks. The Symptom Index of Dyspepsia (SID), Nepean Dyspepsia Symptom Index (NDSI), and Nepean Dyspepsia Life Quality Index (NDLQI) were used to assess treatment efficacy. Functional MRI (fMRI) scans were performed to detect cerebral activity changes at baseline and at the end of the treatment. The results demonstrated that (1) improvements in NDSI, SID, and NDLQI were found in both group A and group B (p < 0.05). However, there were no significant differences in the improvements of the SID, NDSI, and NDLQI scores between group A and group B (p > 0.05); (2) all FD patients showed significantly increased amplitude of low-frequency fluctuation (ALFF) in the left postcentral gyrus after acupuncture treatment, and the changes of ALFF in the left postcentral gyrus were significantly related to the improvements of SID scores (r = 0.358, p = 0.041); and (3) needling at CV12 significantly decreased the resting-state functional connectivity (rsFC) between the left postcentral gyrus and angular gyrus, caudate, middle frontal gyrus (MFG), and cerebellum, while needling at ST36 significantly increased the rsFC between the left postcentral gyrus with the precuneus, superior frontal gyrus (SFG), and MFG. The results indicated that CV12 and ST36 shared similar therapeutic effects for dyspepsia, with common modulation on the activity of the postcentral gyrus in FD patients. However, the modulatory pattern on the functional connectivity of the postcentral gyrus was different. Namely, stimulation of CV12 primarily involved the postcentral gyrus–reward network, while stimulation of ST36 primarily involved the postcentral gyrus–default mode network circuitry.